1967
DOI: 10.2307/1933412
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Savanna Vegetation of the Llanos of Colombia

Abstract: The Llanos Orientales of Colombia are between 3° and 7° lat N, extending as a level plain between 600 and 200 m above sea level, east of the Andes Mountains. The hot tropical climate shows a seasonal pattern of rainfall, divided between one rainy season and one dry season. In the survey of a 45,000—square—mile study area within this llanos region, 10 savanna types were recognized and classified on a floristic basis. Three of these types were floristically distinct, but with the homologous factor of all having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 17 publications
1
50
0
7
Order By: Relevance
“…To consider the possibility that these interpolations overestimated the precipitation values, the precipitation maps of the Geographic Institute Agustin Codazzi (IGAC) were consulted. Focusing on high precipitation areas in the Colombian savanna, similar high rates were found in the corresponding region with values ranging from 4,000 to 5,000 mm per year (IGAC 2002) and as early as 1967, Blydenstein observed that in the Llanos Orientales ''total annual rainfall ranged between 1,700 and 2,000 mm, increasing sharply near the base of the mountains to over 4,000 mm at Villavicencio'' (Blydenstein 1967). It is therefore possible that in this region with steep precipitation gradients and few meteorological stations, the high precipitation rates at Villavicencio have been extrapolated over a region that is too large in area.…”
Section: False Prediction Of Absence (Forest)mentioning
confidence: 64%
See 2 more Smart Citations
“…To consider the possibility that these interpolations overestimated the precipitation values, the precipitation maps of the Geographic Institute Agustin Codazzi (IGAC) were consulted. Focusing on high precipitation areas in the Colombian savanna, similar high rates were found in the corresponding region with values ranging from 4,000 to 5,000 mm per year (IGAC 2002) and as early as 1967, Blydenstein observed that in the Llanos Orientales ''total annual rainfall ranged between 1,700 and 2,000 mm, increasing sharply near the base of the mountains to over 4,000 mm at Villavicencio'' (Blydenstein 1967). It is therefore possible that in this region with steep precipitation gradients and few meteorological stations, the high precipitation rates at Villavicencio have been extrapolated over a region that is too large in area.…”
Section: False Prediction Of Absence (Forest)mentioning
confidence: 64%
“…At the same time, the length of the dry season increases from 2 to 5 months (San José et al 1998). The small annual temperature amplitude of <3°C contrasts with the daily variation of 10-15°C (Blydenstein 1967).…”
Section: Setting Of the Study Areamentioning
confidence: 81%
See 1 more Smart Citation
“…(Correa, Ruiz & Arévalo, 2005). Las formaciones vegetales más representativas son bosques de estrato arbóreo con elementos de 18 y 30 m de altura, herbazales con elementos leñosos, pastizales con resto de bosque, pastizales con elementos de 20 cm de altura donde domina Paspalum carinatum y palmares con predominio de Socratea exorrhiza e Iriartea deltoidea (Blydenstein, 1967;. Este tipo de vegetación se ha modificado desde el siglo XX por la actividad ganadera y por el establecimiento y consolidación de la agricultura comercial basada en cultivos de palma de aceite, arroz, maíz, sorgo, soya, frutales, entre otros (Rippstein, Escobar & Motta, 2001;Mora Fernández, Castellanos, Cardona, Pinzón & Vargas, 2011).…”
Section: Materiales Y Métodosunclassified
“…La siembra de palma de aceite a escala industrial, ha generado impactos negativos en diversos componentes de la biodiversidad (Aratrakorn, Thunhikorn & Donald, 2006;Fitzherbert et al, 2008;Edwards et. al., 2010;García-Ulloa, Sloan, Pacheco, Ghazoul & Pin Koh, 2012), a través de la degradación de hábitat, destrucción y reemplazamiento de la vegetación nativa, que en el caso de la Orinoquía afecta a bosques húmedos, bosques secos, bosques de galería, pastizales y humedales (Blydenstein, 1967;Bolwing, Pomeroy, Tushabe & Mushabe, 2006;Pinzón, Pardi, Trejos & Midori, 2009), lo que genera cambios en la composición y estructura de la vegetación (Correa & Stevenson, 2010).…”
unclassified